2012
DOI: 10.1007/s00355-012-0715-x
|View full text |Cite
|
Sign up to set email alerts
|

On the generalization and decomposition of the Bonferroni index

Abstract: A simple algorithm is proposed which defines the Bonferroni index as the product of a row vector of individual population shares, a linear mathematical operator called the Bonferroni matrix and a column vector of income shares. This algorithm greatly simplifies the decomposition of the Bonferroni index by income sources or classes and population subgroups. The proposed algorithm also links the Bonferroni index to the concepts of relative deprivation and social welfare and leads to a generalization where the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Recently, the Bonferroni index has been revalued since its features and new interesting applications in social and economic contexts have been studied (Barcena-Martin and Silber [8], [9], [10]; Chakravarty and Muliere [18]; Chakravarty [13]).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Bonferroni index has been revalued since its features and new interesting applications in social and economic contexts have been studied (Barcena-Martin and Silber [8], [9], [10]; Chakravarty and Muliere [18]; Chakravarty [13]).…”
Section: Introductionmentioning
confidence: 99%
“…The Gini index for such a partitioned distribution can be written as Ebert (1988b) in their characterizations, it is not included as a member of the generalized entropy family and the Ebert family. Barcena-Martin and Silber (2013) decomposed the Bonferroni index for a population partitioned according to income classes and showed that in addition to between-and within-group components, a residual term, reflecting the effect of ranking and the index's failure to fulfill DPP, appears in the decomposition.…”
mentioning
confidence: 99%
“…To measure the effect of the differences in size (n), we compare the case when the subgroups have different sizes ( f j = 1/J) to the case when the sizes are equal ( f j = 1/J). To make the subgroups have the same size, the least common multiple (lcm) is 2 For the expressions of B w , B b and B i in the case of income classes, see Tarsitano (1990), while for the matrix decomposition of B see Bárcena-Martin and Silber (2013). calculated for the sizes of the analyzed subgroups and the values x ji are repeated lcm times; this leads to equality in size between the subgroups. When applying such an approach to B, the objection is usually raised that B, as opposed to R, does not satisfy the Dalton (1925) principle of being replication invariant.…”
Section: The Shapley Decompositionmentioning
confidence: 99%
“…Piesch (1975) and Nygård and Sandström (1981) were the first to investigate B in depth. New and interesting interpretations and extensions of B have been just recently proposed: its welfare implications have been studied by Benedetti (1986), Aaberge (2000), Chakravarty (2007) and Bárcena-Martin and Silber (2013). Giorgi and Crescenzi (2001c) proposed a poverty measure based on B, while other socio-economic aspects have been studied by Bárcena-Martin and Olmedo (2008), Silber and Son (2010), Silber (2011, 2013), and Imedio Olmedo et al (2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation